1986
DOI: 10.1002/chin.198612287
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Search for New Ca++ Antagonists. Lipophilic Oximes and Phosphonates.

Abstract: Das Nitril (I) reagiert mit den Dioxolanylalkylbromiden (II) über (III) zu den Aldehyden (IV).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Chemistry. The reaction pathways used to synthesise the designed compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) are described in Schemes 1-4 and their chemical and physical characteristics are reported in Table 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemistry. The reaction pathways used to synthesise the designed compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) are described in Schemes 1-4 and their chemical and physical characteristics are reported in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…For several years we have been involved in the design and synthesis of L-type calcium channel antagonists related to verapamil, and we decided to take advantage of the experience accumulated during this researche to design and study N-type calcium channel antagonists. Indeed, during the past decade, it was found that the classic L-type antagonists are not that specific, as a few of them show some action also on other types of calcium channels, namely the N-type.…”
Section: Introductionmentioning
confidence: 99%